Detection of Feigned Crime-Related Amnesia: A Multi-Method Approach - Giger, Peter; Merten, Thomas; Merckelbach, Harald; Oswald, Margit (Journal of forensic psychology practice, 2010)
Claims of crime-related amnesia appear to be common. Using a mock crime approach, the diagnostic power of seven symptom validity instruments was investigated. Sixty participants were assigned to three conditions: responding honestly; feigning crime-related amnesia; feigning amnesia with a warning not to exaggerate. High sensitivity and specificity were obtained for the Structured Inventory of Malingered Symptomatology, the Amsterdam Short-Term Memory Test, and the Morel Emotional Numbing Test. Only three warned malingerers went undetected. The results demonstrate that validated instruments exist to support forensic decision making about crime-related amnesia. Yet, warning may undermine their effectiveness, even when using a multi-method approach.